Meta-analyses of IL1A polymorphisms and the risk of several autoimmune diseases published in databases. - Hang Su; Na Rei; Lei Zhang; Jiaxiang Cheng (PLoS ONE)
Background Based on published data, we aimed to quantitatively elucidate the possible genetic influence of rs17561 G/T and rs1800587 C/T polymorphisms of the IL1A (interleukin 1 alpha) gene in the susceptibility to several autoimmune diseases. Methods A series of meta-analyses were carried out. After database searching, we utilized our inclusion/exclusion criteria to screen and include the eligible studies. Passociation (P value of association test), Bonferroni-corrected Passociation value; false discovery rate (FDR)-corrected Passociation, ORs (odd ratios), and 95% CI (confidence interval) were generated to assess the magnitudes of genetic relationships. Results A total of 35 eligible articles were included. Pooled analysis data of both rs17561 G/T and rs1800587 C/T in the overall population indicated a negative association between cases of autoimmune diseases and negative controls (all Passociation>0.05, Bonferroni-corrected Passociation>0.05, FDR-corrected Passociation>0.05). Similar results were found in most subgroup analyses (all Passociation>0.05, Bonferroni-corrected Passociation>0.05, FDR-corrected Passociation>0.05), apart from the rs1800587 in the Graves' disease subgroup, which showed an increased risk in some cases, compared with controls, under the models of allele T vs. C, carrier T vs. C, CT+TT vs. CC, and CT vs. CC (all Passociation<0.05, Bonferroni-corrected Passociation<0.05, FDR-corrected Passociation>0.05, OR>1). Conclusion Based on the available data, C/T genotype of the rs1800587 polymorphism within IL1A gene may be associated with an increased Graves' disease risk. We did not see evidence regarding a positive role for rs1800587 or rs17561 in the risk of other autoimmune diseases, such as systemic sclerosis or rheumatoid arthritis. These conclusions still merit further data support and molecular exploration.